Metal-Free Thiolation and Hydroxylation of CF3-Substituted Alkenes: A Practical Method to Synthesize Trifluoromethyl Tertiary Alcohols - Niu, Jiapan; Liu, Bowen; Zhang, Chun (Synthesis, 2022)
A novel and practical method to synthesize trifluoromethyl tertiary alcohols has been developed. Under mild reaction conditions, the present reaction could be compatible with a wide range of functional groups. Moreover, the performance of gram-scale reaction and further transformations illustrated the good potential utility of the present chemistry. Furthermore, the radical process of this reaction has been proved by mechanistic studies.
Keywords: alcohols; fluorine; green chemistry; radical reaction; regioselectivity